Internal Capabilities and Sustainable Economic Performance of SMEs: A Resource-Based Systematic Review - Alwan Sri Kustono; Wahyu Agus Winarno; Siti Maria Wardayati; Ardhya Yudistira Adi Nanggala (Global Research and Collaboration, 2026)
This study aims to systematically synthesize how the configuration of internal capabilities drives sustainable profit growth in Small and Medium Enterprises from a Resource-Based View perspective. This research employs a Systematic Literature Review guided by the PRISMA 2020 protocol and analyzes 121 peer-reviewed journal articles indexed in Scopus and published between 2020 and 2025. The review focuses on three critical internal capabilities, namely the utilization of digital technology, accounting, and entrepreneurial capability, and examines their roles in shaping sustainability-oriented performance outcomes. The findings demonstrate that accounting capability is a core, knowledge-based capability. Digital technology is as a strategic enabler depends on its integration with firm-specific internal capabilities. Entrepreneurial capability emerges as an orchestrating capability that aligns accounting and digital capabilities. The synthesis reveals that the interaction and configuration of internal capabilities best explain sustainable profit growth in SMEs. The results contribute to theory by extending the RBV toward an integrative, dynamic perspective, positioning sustainable profit growth as a strategic outcome of internal capability configuration. The findings suggest that SME upgrading strategies and public policy interventions prioritize strengthening accounting and entrepreneurial capabilities alongside digitalization initiatives to achieve long-term economic resilience and sustainability.